Решаем отдельно
Вторая система
![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx-4-2%3C0%7D+%5Catop+%7B-x%2B4%2B2%3C3%7D%7D+%5Cright.+%5Cto+%5Cleft+%5C%7B+%7B%7Bx%3C6%7D+%5Catop+%7Bx%3E3%7D%7D+%5Cright.+%5Cto+%283%3B6%29)
3}} \right. \to (3;6)" alt=" \left \{ {{x-4-2<0} \atop {-x+4+2<3}} \right. \to \left \{ {{x<6} \atop {x>3}} \right. \to (3;6)" align="absmiddle" class="latex-formula">
Теперь
Решив отдельно, получаем
![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7B-x%2B4-2+%5Cgeq+0%7D+%5Catop+%7B-x%2B4-2%3C3%7D%7D+%5Cright.+%5Cto+%5Cleft+%5C%7B+%7B%7Bx+%5Cleq+2%7D+%5Catop+%7Bx%3E-1%7D%7D+%5Cright.+%5Cto%28-1%3B2%5D)
-1}} \right. \to(-1;2]" alt=" \left \{ {{-x+4-2 \geq 0} \atop {-x+4-2<3}} \right. \to \left \{ {{x \leq 2} \atop {x>-1}} \right. \to(-1;2]" align="absmiddle" class="latex-formula">
Второе
![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7B-x%2B4-2%3C0%7D+%5Catop+%7Bx-4%2B2%3C3%7D%7D+%5Cright.+%5Cto+%5Cleft+%5C%7B+%7B%7Bx%3E2%7D+%5Catop+%7Bx%3C5%7D%7D+%5Cright.+%5Cto+%28-1%3B5%29)
2} \atop {x<5}} \right. \to (-1;5)" alt=" \left \{ {{-x+4-2<0} \atop {x-4+2<3}} \right. \to \left \{ {{x>2} \atop {x<5}} \right. \to (-1;5)" align="absmiddle" class="latex-formula">
Объеденим и получаем ответ
Ответ: